2018
DOI: 10.1177/2515841418815802
|View full text |Cite
|
Sign up to set email alerts
|

Corneal endothelial cell dysfunction: etiologies and management

Abstract: A transparent cornea is essential for the formation of a clear image on the retina. The human cornea is arranged into well-organized layers, and each layer plays a significant role in maintaining the transparency and viability of the tissue. The endothelium has both barrier and pump functions, which are important for the maintenance of corneal clarity. Many etiologies, including Fuchs’ endothelial corneal dystrophy, surgical trauma, and congenital hereditary endothelial dystrophy, lead to endothelial cell dysf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
101
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(111 citation statements)
references
References 179 publications
(277 reference statements)
1
101
0
9
Order By: Relevance
“…Other components of the immune milieu, including various cytokines and mediator cells, contribute to the decompensation of the corneal endothelium when their balance shifts [42,49]. Corneal edema and bullous keratopathy often signal graft failure, and these conditions are often characterized by dystrophic changes in the Descemet's membrane and stroma that are partially, if not largely, caused by immune responses [50]. Keratocytes within the epithelium and stroma, endothelial cells, and immune cells brought to the cornea through homing mechanisms all contribute to the corneal immune response through cytokine and chemokine secretion, assisted by the expression of various adhesion proteins in the corneal cells [21,24,26,[28][29][30][34][35][36][37].…”
Section: Cytokines and Regulatory T Cellsmentioning
confidence: 99%
“…Other components of the immune milieu, including various cytokines and mediator cells, contribute to the decompensation of the corneal endothelium when their balance shifts [42,49]. Corneal edema and bullous keratopathy often signal graft failure, and these conditions are often characterized by dystrophic changes in the Descemet's membrane and stroma that are partially, if not largely, caused by immune responses [50]. Keratocytes within the epithelium and stroma, endothelial cells, and immune cells brought to the cornea through homing mechanisms all contribute to the corneal immune response through cytokine and chemokine secretion, assisted by the expression of various adhesion proteins in the corneal cells [21,24,26,[28][29][30][34][35][36][37].…”
Section: Cytokines and Regulatory T Cellsmentioning
confidence: 99%
“…Specular microscopy is a noninvasive method for analyzing the corneal endothelium and facilitates the rapid and correct diagnosis of corneal endotheliopathy affecting the structure and physiology of this corneal layer [ 14 - 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the rate of cataract surgery growing exponentially, 14 cataract surgery, typically phacoemulsification, is the most common cause of corneal endothelial decompensation. [30][31][32][33][34][35] Corneal endothelium decompensation occurs as a surgical complication in 1 to 2% of cataract surgeries. 30,36,37 Cornea edema after cataract surgery was the predominant indication for penetrating keratoplasty in North America (28.0%) and ranked second in Europe (20.6%), Australia (21.1%), the Middle East (13.6%), Asia (15.5%), and South America (18.6%).…”
mentioning
confidence: 99%
“…[30][31][32][33][34][35] Corneal endothelium decompensation occurs as a surgical complication in 1 to 2% of cataract surgeries. 30,36,37 Cornea edema after cataract surgery was the predominant indication for penetrating keratoplasty in North America (28.0%) and ranked second in Europe (20.6%), Australia (21.1%), the Middle East (13.6%), Asia (15.5%), and South America (18.6%). 35 In previous studies, staining for 8-hydroxy-2deoxyguanosine (8-OHdG), a marker of oxidative stress, has revealed that the free radicals produced by phacoemulsification cause damage to the corneal endothelium.…”
mentioning
confidence: 99%